Teacup full of roses - Mathis, Sharon Bell. (New York : Puffin Books, 1987)
Joe's decision to leave home is prompted by despair over his mother's blindness to his younger brother's talents and his older brother's drug addiction.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Junior High School.
Booklist, May 1997.
Horn Book, April 1999.
Kirkus Review, October 1999.
Keywords: Dysfunctional families -- Juvenile fiction; Family life -- Fiction; Family problems -- Fiction; Family life -- Fiction; Family problems -- Fiction